Perceptions of faculty members on the value of distance education at two different types of institutions of higher education in the Kingdom of Saudi Arabia - Alsuelmi, Alaa Abdulrahman (Kansas State University, 2021)
With the current rapid and forced adoption of online teaching during COVID-19 pandemic in many parts of the globe, the need for more studies for the burden faculty members will face to improve online learning will increase. This study aimed to examine the perceptions of faculty in Qassim University (QU) and Princess Nourah University (PNU) in Saudi Arabia toward distance education. For this purpose, the quantitative approach was used using an online survey instrument, quantitative data were collected from 122 faculty members. Findings of this study may encourage administrators in the KSA’s higher education institutions to make key policy and process decisions that focus on improving the quality of online teaching. Understanding the influence (positive or negative) of faculty perceptions on online learning can help inform their decisions. The sample of the study consisted of 122 faculty members of faculty in Qassim University (QU) and Princess Nourah University (PNU) in Saudi Arabia. Findings from this particular study at both Universities have shown promising evidence that faculty members had a positive attitude toward online courses to some extent. The findings failed to support the null hypothesis of no difference for perceived value of distance education, and institutional support of online education regarding the influence of institutional support of online education on faculty perceptions of distance education. The results indicated that as length of institutional support of online education increases, satisfaction with effectiveness of online learning also increases. Faculty perceived value of distance education were also found to be related to the individual’s perceptions of distance education. As the perceived value of distance education were more positive, so too does satisfaction with effectiveness of online learning. Theoretically, the findings of the current study are in concert with earlier research by Herzberg (1985) whose two-factor theory attributed increased responsibility advancement, and achievement to satisfaction.
Keywords: Saudi Arabia; University; Faculty; COVID-19; Princess Nourah University; Qassim University